Математическое моделирование топочных процессов при факельном сжигании твердого топлива - Гиль А. В. Андрей Владимирович; Мальцев К. И. Кирилл Иванович; Заворин А. С. Александр Сергеевич; Старченко А. В. Александр Васильевич (2022, 2022)
Заглавие с экрана